2015
DOI: 10.3174/ajnr.a4487
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Internal Carotid Artery Occlusion for Large and Giant Aneurysms: A Single Center Cohort of 146 Patients

Abstract: BACKGROUND AND PURPOSE: At our institution, patients with large or giant ICA aneurysms are preferably treated with endovascular ICA balloon occlusion. Alternative treatment or conservative treatment is offered only for patients who cannot tolerate permanent ICA occlusion. In this observational study, we report the clinical and imaging results of ICA occlusion for aneurysms in a large single-center patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Furthermore, if the patient’s artery did not have sufficient collateral blood flow, bypass surgery (i.e., STA-MCA [superficial temporal artery-to-middle cerebral artery] anastomosis or a high flow) would be required. 18 20) On the other hand, FDs are ideal treatment devices because they promote endoluminal and neointimal growth leading to parent vessel reconstruction while preserving antegrade blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if the patient’s artery did not have sufficient collateral blood flow, bypass surgery (i.e., STA-MCA [superficial temporal artery-to-middle cerebral artery] anastomosis or a high flow) would be required. 18 20) On the other hand, FDs are ideal treatment devices because they promote endoluminal and neointimal growth leading to parent vessel reconstruction while preserving antegrade blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Managing a cavernous ICA acute injury is a complex issue, as it involves rapid blood loss originating from a challenging to reach anatomical area. There are three options to treat such a condition: ICA sacrifice, ICA lesion embolization, and ICA endoluminal reconstruction [1][2][3][4][5][6]9].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, careful preoperative evaluation with a BTO is required prior to ICA sacrifice. In a large case series of 88 patients treated with ICA occlusion for aneurysms, Bechan et al 17 reported three subclinical infarcts and three patients with a transient hemiparesis, all of which were in the watershed territory between the anterior and middle cerebral artery. The only permanent complication in their series was a hypoperfusion infarction due to a retroperitoneal hematoma.…”
Section: Discussionmentioning
confidence: 99%